2019
DOI: 10.28991/cej-2019-03091226
|View full text |Cite
|
Sign up to set email alerts
|

Green and Sustainable Concrete – The Potential Utilization of Rice Husk Ash and Egg Shells

Abstract: Concrete which is widely used material in the construction industry, has a carbon footprint. Approximately 10% of global Carbon Dioxide (CO2) gas is emitted during the production of cement which is vital ingredient of concrete. The increase in production of cement affects global warming and climate change. Therefore, many have attempts have been made to develop green and sustainable concrete by utilizing different waste materials. With the utilization of waste materials as cement replacement, the CO2 gas emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 22 publications
0
19
0
4
Order By: Relevance
“…Calcium-rich ESP has a similar chemical composition to the cement. Furthermore, ESP comprises the approximately same amount of CaO as cement [7,8]. On the other hand, FA also contains some pozzolanic minerals viz.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium-rich ESP has a similar chemical composition to the cement. Furthermore, ESP comprises the approximately same amount of CaO as cement [7,8]. On the other hand, FA also contains some pozzolanic minerals viz.…”
Section: Introductionmentioning
confidence: 99%
“…ESP is a smooth surface and it is grainded by the machines. From the good quality of eggshells 2.2 grams of calcium carbonate is generated and which is used as cement [3][9] [16]. In the every drt eggshell, 95 percentage of calcium content is available [7][10] [15].Eggshells are waste products from bakeries, fast food restaurants, and chick hatcheries.…”
Section: B Eggshell Powder (Esp)mentioning
confidence: 99%
“…Eggshell is another waste available in abundance in Malaysia and is rich in calcium oxide (CaO). Eggshells are considered to be of no practical value; therefore, without any treatment, they are disposed of in the landfills causing significant environmental pollution (Jhatial et al, 2019a;Raji and Samuel, 2015). Interestingly, eggshells powder (ESP) has been used as SCMs, and it was found that replacement of 5% to 7.5% of cement is possible (Wei et al, 2020;Jhatial et al, 2019b;Ujin et al, 2017;Dhanalakshmi et al, 2015;Gowsika et al, 2014;Yerramala, 2014).…”
Section: Introductionmentioning
confidence: 99%